Nonisotopic ultrastructural mapping of transcription sites within the nucleolus - Dundr, M; Raska, I (Experimental cell research, 1993)
A nonradioactive ultrastructural method based on the incorporation of 5-bromouridine-5'-triphosphate into the RNA of streptolysin O-permeabilized cultured HeLa cells is described and used for the visualization of rRNA transcription sites. Even though the method provides much better resolution than ultrastructural autoradiography, the results obtained do not allow the assignment of rRNA transcription to a single nucleolar structural component. We locate the rRNA transcription sites at the border region of fibrillar centers with dense fibrillar components. In addition, the method represents a convenient tool for the in situ immunodetection of extranucleolar RNA synthesis.
Keywords: Uridine Triphosphate; HeLa Cells; Microscopy, Electron; In Vitro Techniques; buněčné jadérko; uridintrifosfát; Cell Nucleolus; Humans; techniky in vitro; RNA ribozomální; RNA, Ribosomal; Transcription, Genetic; HeLa buňky; lidé; genetická transkripce; elektronová mikroskopie